2014
DOI: 10.3201/eid2001.120101
|View full text |Cite
|
Sign up to set email alerts
|

Contact Tracing for Influenza A(H1N1)pdm09 Virus–infected Passenger on International Flight

Abstract: In April 2009, influenza A(H1N1)pdm09 virus infection was confirmed in a person who had been symptomatic while traveling on a commercial flight from Mexico to the United Kingdom. Retrospective public health investigation and contact tracing led to the identification of 8 additional confirmed cases among passengers and community contacts of passengers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Two investigations (one historical cohort study and one retrospective investigation) apparently reported about the same flight. 23 , 24 However, both studies were included in our analysis, as different contact tracing strategies were applied and resulting data differed (e.g., the number of index cases, secondary cases, passengers traced, and passengers aboard). The other 16 articles were excluded as they reported findings using modeling techniques and experimental approaches rather than analyzing actual transmission events aboard aircraft.…”
Section: Resultsmentioning
confidence: 99%
“…Two investigations (one historical cohort study and one retrospective investigation) apparently reported about the same flight. 23 , 24 However, both studies were included in our analysis, as different contact tracing strategies were applied and resulting data differed (e.g., the number of index cases, secondary cases, passengers traced, and passengers aboard). The other 16 articles were excluded as they reported findings using modeling techniques and experimental approaches rather than analyzing actual transmission events aboard aircraft.…”
Section: Resultsmentioning
confidence: 99%
“…Only reported in case of secondary infections and in these cases infections may also occur before or after the flight. [118,[124][125][126][127]…”
Section: Retrospectivementioning
confidence: 99%
“…In April 2009, on a 9.5-hour flight from Mexico to Birmingham, UK, a passenger contagious with novel H1N1 virus infected 6 passengers. 22 Only 2 of the infected passengers were seated within 2 rows of the infectious passenger.…”
mentioning
confidence: 99%